Five new species of Tachydromiinae (Diptera: Empididae s.l.) from New World Tertiary ambers - Kraemer, Mónica M. Solórzano; Sinclair, Bradley J.; Cumming, Jeffrey M. (Zootaxa, 2005)
Five new species of Tachydromiinae (Empididae s.l.) are described, four from Mexican amber (Chaetodromia pulchra sp. nov., Drapetis dissentis sp. nov., Micrempis brevis sp. nov., Stilpon mexicanus sp. nov.) and one from Dominican amber (Chersodromia dominicana sp. nov.). These are the first tachydromiine species described from New World Tertiary (Oligocene-Miocene) ambers. Thirty-two Tertiary fossil species of Tachydromiinae are now known worldwide.